Agronomic technology to promote sustainable utilization of newly created farmland in the Chinese Loess Plateau. (29th September 2022) - Li, Yurui; Zhang, Xuanchang; Liu, Yansui; Wang, Yongsheng; Huang, Yunxin; Lu, Zhi; Feng, Weilun; Chen, Zongfeng; Wei, Hong'an
Abstract: The new farmland created by land consolidation often faces the problems of poor soil structure and low productivity, which cause potential degradation risk. The Gully Land Consolidation Program (GLCP) significantly increased the quantity of farmland in the Chinese Loess Plateau (LP), but the research on a comprehensive method of simultaneously improving soil quality, agricultural profit, and utilization efficiency of newly created farmland (NCF) is relatively scant. This study explored an agronomic technology to improve soil quality, agricultural profit, and utilization efficiency NCF by the GLCP in the LP. Our field experiment was carried out in Yangjuangou catchment with seven soil treatments and planting Brassica napus (B. napus) on these soils: dry mixing Malan Loess and red clay at volumetric ratios of 1:0 (MR10), 5:1 (MR51), 2:1 (MR21), 1:1 (MR11), 1:2 (MR12), 1:5 (MR15), and 0:1 (MR01). The results showed that: the soil microstructure, physico‐chemical properties, and productivity of NCF were significantly improved after soil reconstruction by dry mixing Malan Loess and red clay. More specifically, the MR51 boosted the root thickness and fresh weight of B. napus by 78.69% and 45.01% compared to that of red clay (MR01). Crop optimization by the B. napus helped to increase the agricultural profits of NCF. The proposed three portfolios of B. napus ' silage, vegetable plus rapeseed, and vegetable plus silage enhanced the profits by 35.39%, 57.05%, and 66.93% in comparison with that of traditional crop planting, respectively. Therefore, industrial integration through effective, ecological and economic (3E) agriculture could advance sustainable utilization of NCF. Further, developing efficient agriculture, animal husbandry, agricultural products processing industry, and ecological tourism would enhance the multi‐functional value of farmland. Our study suggests that targeted agronomic technology based on agricultural geographical engineering oriented to human‐environment interaction can provide technical support for minimizing the degradation risk of NCF and generating more sustainable development in ecologically fragile areas.